Do children with attention deficit and hyperactivity disorder (ADHD) have a different gait pattern? Relationship between idiopathic toe-walking and ADHD - Víctor Soto Insuga; Beatriz Moreno Vinués; Rebeca Losada del Pozo; María Rodrigo Moreno; Marta Martínez González; Raquel Cutillas Ruiz; Carmen Mateos Carmen (Elsevier, 2018)
Introduction: Idiopathic toe-walking (ITW) is described as a gait pattern with no contact between the heels and the ground in children older than 3 years. The diagnosis is clinical, making it necessary to rule out other neurological and orthopaedic conditions. A relationship between ITW and vestibular dysfunction and/or proprioceptive sensibility has been proposed. Children with neurodevelopmental disorders (autism, language and cognitive disorders) often have ITW. Objectives: To determine the frequency of ITW in children with attention deficit disorder and hyperactivity (ADHD). Patients and method: A study was conducted on children diagnosed with ADHD, with normal neurological examination, with no alterations in MRI scan, cognitive disorder or autism. A complete clinical anamnesis was performed and Achilles shortening was measured with a goniometer. Results: The study included 312 children with a mean age of 11 years (73.7% boys). The ADHD combined subtype was the most frequent (53.8%), followed by the inattentive (44.9%), and hyperactive (1.3%). ITW was observed in 20.8% of patients, particularly in the combined subtype (P = .054). Only 32 of them (49.2%) had Achilles shortening. ITW was associated with sociability disorders (P = .01), absence of pain in legs (P = .022), and family history of ITW (P = .004). Only 11% had previously visited a doctor for this reason. Conclusions: As in other neurodevelopmental disorders, children with ADHD have frequently more ITW and Achilles shortening than controls, especially if they presented with a social communication disorder or a family history of ITW. An early diagnosis is essential to establish effective treatments. Resumen: Introducción: La marcha de puntillas idiopática (MPI) se describe como el patrón de marcha sin apoyo del talón en niños mayores de 3 años. El diagnóstico es clínico y obliga a descartar otras enfermedades neurológicas y traumatológicas-ortopédicas. Se postula su relación con una disfunción vestibular o de sensibilidad propioceptiva. Los niños con trastornos del neurodesarrollo (trastorno del espectro autista, trastorno del lenguaje y cognitivo) presentan frecuentemente MPI. Objetivos: Analizar la frecuencia de MPI en niños con trastorno por déficit de atención e hiperactividad (TDAH). Pacientes y método: Estudio en niños diagnosticados de TDAH con exploración neurológica normal, sin alteraciones en neuroimagen ni trastorno cognitivo o trastorno del espectro autista. Se realizó anamnesis completa y se valoró la presencia de acortamiento aquíleo con goniómetro. Resultados: Se analizó a 312 niños con edad media de 11 años, el 73,7% varones. El subtipo combinado fue el más frecuente (53,8%), seguido del inatento (44,9%) e hiperactivo (1,3%). Un 20,8% de los pacientes presentaban MPI, que era más frecuente en el subtipo combinado (p = 0,054). Solo 32 de estos (49,2%) presentaban acortamiento aquíleo. La presencia de MPI se relacionó con alteraciones en el área de la sociabilidad (p = 0,01), ausencia de dolor en miembros inferiores (p = 0,022) y antecedentes familiares de MPI (p = 0,004). Solo el 11% habían consultado por este motivo previamente. Conclusiones: Al igual que en otros trastornos del neurodesarrollo, los niños con TDAH presentan con mayor frecuencia MPI y acortamiento aquíleo, especialmente entre aquellos con trastornos de comunicación social o antecedentes familiares de MPI. Es fundamental una identificación precoz para instaurar tratamientos eficaces.